Exploring birth experience of mother based on comfort theory - Cicek Okuyan, Yonca; Bolsoy, Nursen; Cetinkaya , Aynur (Journal of the Pakistan Medical Association, 2024)
Objective: To analyse the phenomenon of "giving birth" on the basis of the lived experiences of women and midwives. Method: The qualitative study was conducted in the delivery room of a mother-friendly hospital in western Turkey from March 1 to December 30, 2019, and comprised primiparous women aged 18-35 years having a spontaneous vaginal birth, and midwives who delivered the babies. Data was collected through indepth interviews that were audio-recorded. Additionally, women’s written birth stories and researcher’s observation regarding the participants were used. Data was subjected to content analysis using NVIVO 12 Pro software. Results: Of the 28 subjects 15(53.6%) were lay women with mean age 24.2±3.87 years (range: 18-30 years), and 13(46.4%) were midwives with mean age 42.61±4.50 years (range: 37-50 years). The most referred conceptual themes in Kolcaba’s Theory of Comfort were “enhanced comfort”, “mother-friendly hospital policy”, and “midwives’ comforting interventions.” Under the theme of "Increasing Comfort", women cared about psychological and environmental comfort. Women had the most psychospiritual comfort and environmental comfort as well as physical and sociocultural comfort. Women cared about psychological and environmental comfort that facilitated birth. Conclusion: The mother-friendly hospital policy increased and contributed to the support and comfort provided to women. Kolcaba's Comfort Theory was an appropriate and working theory for birth and midwifery care, indicating that women's comfort should be ensured in the psychospiritual, environmental, physical and sociocultural contexts. Key Words: Parturition, Women, Midwives, Hospital, Patient comfort.